The The Effects of Internal Audit, Effectiveness, and Gender Diversity of Audit Committee on Audit Fee - Pandhadha, Raditya Waskitha; Wijayanti, Anita (TEMA, 2025)
The objective of this study is to assess and analyze the impacts of internal audit, effectiveness, and gender diversity of the audit committee on audit fees. The data was harvested from the annual reports of 52 property and real estate companies listed on the Indonesia Stock Exchange in 2023. The results of the analysis indicate that the audit's internal functions positively influence the audit fee. The audit committee's effectiveness was assessed by measuring its proxies with the following results. Audit committee size, audit committee’s meeting frequency, and audit committee expertise have no effect on audit fees, and the committee’s gender diversity also has no effect on the audit fee. The positive effects indicate the presence of the internal audit functions supporting the demand perspective, where the better the resources in the company, the more quality audits will be demanded. On the contrary, the absence of the effect of audit committee effectiveness and gender diversity of the audit committee on audit fees indicates an opposition to both the demand perspective and the supply perspective.